How the Liberation Day Announcement is Shaping the Global Trade Order: From Free Trade to Fair Trade Agreements - Ojo, Marianne (Journal of Finance Research Letters, 2025)
It may be assumed that all of the United States’ trading partners were impacted by the recent “Liberation Day” announcement – an announcement which constitutes “two distinct tariff actions” – as will be highlighted in this paper. However, despite previous concerns of being targeted by their free trade agreement (FTA) partner, Canada and Mexico – as would have been or should be expected, have been exempted from the tariff imposition. As well as addressing factors which have contributed to the shift from free trade to increasingly and predominantly protectionist stances and most likely, fair trade practices, this paper is aimed at highlighting and explaining the rationales behind the recent historical developments – as well as highlighting those factors that have triggered the build up to the Liberation Day Announcement of the 2nd April 2025. It is remarked that “Trump’s reciprocal tariff doctrine, holds foreign countries accountable”. Against this backdrop of discontent with World Trade Organisation’s dispute resolution mechanisms, which will be further elaborated on, in the paper, the immediate and possible long term impacts of the Announcement, will be considered. As well as exploring the reasons for recent developments – by way of reference to historical developments and data, the paper also considers the underlying frameworks governing the calculations of recent tariff rates and hikes. Whilst there are arguments regarding the validity of such calculations, or whether the current scenario justifies the basis for implementing “national emergency measures”, what can be regarded as an emergency response can be determined through a consideration of underlying and contributory factors. If negotiations, and more specifically, bilateral negotiations, take place as hoped, between those countries impacted by the Liberation Day Announcement, financial stability across global markets is expected to be restored. However, if retaliatory measures follow – with an escalation of trade wars, possible repercussions should be cause for concern. The global trading system is still recovering from the recent crisis which was largely uncontrollable – hence, it is more likely (and hoped) that the recent market turbulence and volatilities will be short term.
Keywords: Deregulation; Dispute resolution mechanisms; Financial stability; Free trade agreements; Manufacturing; Monetary policy; Protectionism; World Trade Organisation

A path to paperless trade: analysing the legal gaps and economic benefit of adopting or maintaining a legal framework that takes into account the UNCITRAL Model Law on Electronic Transferable Records (MLETR) - Committee on Trade and Investment (CTI) (Asia-Pacific Economic Cooperation, 2025)
Keywords: Asia and the Pacific; DIGITAL TECHNOLOGY; ELECTRONIC COMMERCE; UN Convention on the Use of Electronic Communications in International Contracts (2005); UNCITRAL Model Law on Electronic Commerce (1996); UNCITRAL Model Law on Electronic Transferable Records (2017)

Internationality overreach in the interpretation of uniform private law conventions: the Contra Proferentem rule and the CISG - Kryla-Cudna, Katarzyna (International and comparative law quarterly, 2025)
This article argues that the rule of contra proferentem is not applicable to international sales contracts governed by the United Nations Convention on Contracts for the International Sale of Goods (CISG). It further argues that the common recognition of the rule of contra proferentem under the CISG is an instance of a broader phenomenon which it calls ‘internationality overreach’. ‘Internationality overreach’ is the tendency to project onto the provisions of a uniform private law instrument doctrines and concepts which are inaccurately presumed to constitute universally recognised principles of private law or the ‘common core’ of various legal systems. This article demonstrates that internationality overreach disrupts the goals underpinning the harmonisation of commercial law in two ways: first, it undermines uniformity in the application of international conventions; and, second, it leads to outcomes that fall short of the agreement reached by the Contracting States during the drafting process. While this article focuses on the CISG, the argument developed in this article is of equal relevance to other uniform private law conventions which follow the principle of autonomous interpretation.
Keywords: INTERNATIONAL SALE OF GOODS; INTERNATIONAL TRADE LAW; UN Convention on Contracts for the International Sale of Goods (1980)